2020
DOI: 10.3892/or.2020.7690
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA SNHG3 promotes breast cancer�progression by acting as a miR‑326 sponge

Abstract: Accumulating evidence suggests that long noncoding RNA (lncRNA) small nucleolar RNA host gene 3 (SHNG3) plays crucial roles in the initiation and progression of various types of malignant cancers. Yet, the role played by SNHG3 in breast cancer as well as the associated mechanisms remain largely unclear. The expression of SNHG3 was detected in breast cancer tissues and cell lines by reverse-transcription quantitative PCR (RT-qPCR). Cell proliferation, colony formation, cell cycle distribution, migration and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The mechanism studies of LncRNAs showed that lncRNAs could regulate genes expression as miRNA sponges [ 21 , 22 ]. Therefore, the potential target miRNAs of SNHG10 were predicted by bioinformatics analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism studies of LncRNAs showed that lncRNAs could regulate genes expression as miRNA sponges [ 21 , 22 ]. Therefore, the potential target miRNAs of SNHG10 were predicted by bioinformatics analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the role of SNHG3 in caner has been gradually uncovered [30]. Increasing studies indicated that SNHG3 affects the tumor development and progression by regulating autophagy-related microRNAs, genes, or corresponding pathways [31][32][33][34]. MIR210HG [35][36][37][38], and ZEB1-AS1 [39,40] have also been found to affect tumorigenesis, progression, and tumor metastasis, resulting in a poor prognosis for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG3 exhibits characteristic oncogenic properties in multiple cancers. Studies have indicated that SNHG3 is significantly upregulated in hepatocellular carcinoma (HCC)[ 25 , 26 ] and other cancers, such as cervical cancer (CC)[ 27 , 28 ], and breast cancer (BC)[ 29 - 34 ]. Clear cell renal cell carcinoma (ccRCC)[ 35 ], colorectal cancer (CRC)[ 36 - 38 ], glioma[ 39 , 40 ], HCC[ 25 , 41 , 42 ], non-small cell lung cancer (NSCLC)[ 43 - 47 ], ovarian cancer (OC)[ 48 - 51 ], and papillary thyroid carcinoma (PTC)[ 52 ].…”
Section: Clinical Characters Of Lncrna Snhg3mentioning
confidence: 99%
“…HCC growth was inhibited in vivo due to the knockdown of the SNHG3 gene[ 25 ]. Similarly, SNHG3 gene knockdown inhibited the growth of other tumors, such as BC[ 34 ], CC[ 27 ], ccRCC[ 35 ], CRC[ 36 , 37 ], GC[ 77 ], glioma[ 40 ], laryngeal carcinoma[ 80 ], NSCLC[ 45 , 46 ], OC[ 49 ], PTC[ 52 ], prostate cancer[ 85 ]. Overall, SNHG3 promoted the progression of the abovementioned tumors.…”
Section: Snhg3 In Vivo Studiesmentioning
confidence: 99%